Rachunek kosztów w przedsiębiorstwach gospodarki żywnościowej - Wyszkowska, Zofia (The Count of Costs in Food Economy Businesses, 2005)
In this article the information about running the count of costs in farm businesses are presented. 41 businesses were analyzed. The data showed different methods of running the count of costs used in farm businesses, bakeries and dairies. In all busineses there are used different kinds of counts of costs which are not modern and not perfect and they need to be improved. The way they function nowadays can not satisfy the managements of businesses.(original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1085, s. 391-398